Association of plasma concentration of trace metals with frontotemporal degeneration - DeLano, Kelly; Sprague, Alex C.; Jandarov, Roman; Jackson, Brian P.; Shatz, Rhonna; Langevin, Scott M.; Sawyer, Russell P. (Frontiers in Neurology, 2025)
ObjectiveCompare the burden of heavy metals in plasma from people with frontotemporal degeneration (FTD) and healthy controls.MethodsA cross-sectional study of 14 FTD cases and 28 healthy controls recruited from the University of Cincinnati. Plasma samples were sent to the Trace Element Analysis Core at Dartmouth College for assessment of 24 metals or metalloids via inductively coupled plasma mass spectrometry (ICP-MS). Unconditional logistic regression models were performed with adjustments for age (centered at the median) and sex.ResultsAfter adjusting for age and sex, there was a significant positive association of FTD with the highest tertile of Manganese (ORadjusted = 11.1, 95% CI: 1.57–132) and Chromium (ORadjusted = 9.86, 95% CI: 1.24–218). There was significant inverse associations observed between FTD and the highest tertile of Barium (ORadjusted = 0.06, 95% CI: <0.01–0.47) and Mercury (ORadjusted = 0.13, 95% CI: 0.01–0.74), with a significant inverse trend (ptrend = 0.03).ConclusionSignificant associations between plasma concentration of several trace metals and FTD. The significantly elevated levels of Manganese and Chromium may suggest a role of environmental exposure in the pathogenesis of FTD. However, larger, well-designed prospective studies, along with complementary experimental work, are needed to better elucidate this relationship.